Detection of microphase separation in poly(tert-butyl acrylate-b-methyl methacrylate) synthesized via atom transfer radical polymerization by inverse gas chromatography - Aydin, Sevda; Erdogan, Tuba; Sakar, Dolunay; Hizal, Gurkan; Cankurtaran, Ozlem; Tunca, Umit; Karaman, Ferdane (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
A trace amount of solvents such as n-octane, n-nonane, n-decane, ethyl acetate, n-propyl acetate, isoamyl acetate, toluene, ethyl benzene, n-propyl benzene, isopropyl benzene and chloro benzene was passed through the column of a gas chromatograph of which the stationary phase is poly(tert-butyl acrylate-b-methyl methacrylate), poly(tBA-b-MMA), block copolymer with low polydispersity, prepared via ATRP of tBA and MMA, respectively. The retention diagrams to determine the thermal transition of the polymer were obtained by plotting the logarithm of the specific retention volumes of isoamyl acetate and toluene against reciprocal values of absolute column temperatures between 40 and 170 degrees C by inverse gas chromatography (IGC) technique. Three glass transition temperatures, T(g)s of poly(tBA-b-MMA) were determined at 50, 70 and 105 degrees C by IGC indicating the phase separation of the polymeric blocks in the copolymer. The thermodynamical interaction parameters such as weight fraction activity coefficient of solvent at infinite dilution, Omega(infinity)(1), Flory-Huggins polymer-solvent interaction parameter, chi(infinity)(12), equation-of-state polymer solvent interaction parameter, chi(.)(12), effective exchange energy parameter, X-eff, and solubility parameter of the copolymer, delta(2) were calculated at studied temperatures. The closeness of parameters of the poly(tBA-b-MMA) to those of the PMMA indicated that the continuous phase is MMA block in the microphase separated block copolymer. It seems that IGC is a reliable technique to study a phase separated block copolymer which contains nanosized domains. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: atom transfer radical polymerization (ATRP); inverse gas chromatography; poly(tert-butyl acrylate-b-methyl methacrylate) diblock copolymer; thermal transition; solution properties; microphase separation; BLOCK-COPOLYMERS; POLY(VINYLIDENE FLUORIDE); MIXTURES; Polymer Science